Design guideline of capacitive power transfer system to achieve targeted output power - Supapong Nutwong; Ekkachai Mujjalinvimut; Anawach Sangswang; Nattapong Hatchavanich; Mongkol Konghirun (Institute of Advanced Engineering and Science, 2023)
Power transfer capability of the capacitive power transfer (CPT) system is dependent on the dimensions of capacitive coupler, which should be correctly designed to meet the required amount of output power. This paper presents a guideline to design the conductive plates used in CPT system to achieve a targeted output power. For a given operating frequency, resonant inductance, DC input voltage, load resistance, and the air gap between plates, the required cross-sectional area of conductive plates is obtained using this guideline. It has been guided through the design procedure which is explained in detail. A step-by-step guide to design a 5-watts CPT system is demonstrated as a design example. The proposed design guideline is verified by the experiment which shows the closeness between measured and targeted output power. Design error is obtained as low as 3.6 percent.